Determinan Minat Bereinvestasi Saham pada Generasi Milenial di Komunitas Investor Saham Pemula Regional Pekanbaru - Ichlassul Amal; Rama Gita Suci; Dwi Fionasari (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2023)
This study aims to examine the effect of investment knowledge, motivation, and risk perception on the interest in investing in millennial generation stocks. The sample in this study were members of the Pekanbaru Regional Beginner Stock Investor Community aged 20-40 years and investing no more than 3 years. This type of research is quantitative research with a descriptive approach. The data analysis method used was linear multiple analysis, the data was processed using SPSS Version 24 software. The results showed that the variables of investment knowledge and motivation affected the interest in investing in millennial generation stocks. Meanwhile, the risk perception variable no does not affecterestonn investing in millennial generation stocks.